Ghostbusters : afterlife [videorecording (DVD)] - Reitman, Jason, 1977-; Kenan, Gil; Coon, Carrie, 1981-; Wolfhard, Finn, 2002-; Grace, Mckenna, 2006-; Woodbine, Bokeem; Rudd, Paul; Murray, Bill, 1950 September 21-; Aykroyd, Dan; Hudson, Ernie; Potts, Annie; Weaver, Sigourney, 1949-; et al. (Sony Pictures Home Entertainment, 2022)
When a single mom and her two kids arrive in a small town, they begin to discover their connection to the original Ghostbusters and the secret legacy their grandfather left behind.